Synthesis and photoluminescent properties of water-soluble TbF_3 nanoparticles - 王振领 张新磊 常加忠 李春阳 (Journal of rare earths, 2011)
Monodispersed and water-soluble TbF3 nanoparticles were synthesized at a relatively low temperature in aqueous solution using citric acid as an additive,and characterized by X-ray diffraction（XRD）,field emission scanning electron microscopy（FE-SEM）,Fourier transform infrared spectra（FTIR）,photoluminescence（PL） spectra and lifetime.The as-prepared TbF3 nanoparticles had orthorhombic structure and were composed of monodispersed spherical particles with an average particle size of 50 nm.The excitation spectrum of TbF3 nanoparticles obtained by monitoring the emission of Tb3＋ at 543 nm was composed of the characteristics f-f transition lines within the Tb3＋ 4f8 configuration.Under the UV light irradiation,the emission spectrum exhibited four obvious lines centered at 489,543,589,and 618 nm,which was corresponding to the 5D4→7FJ（J=6,5,4,3） transitions of the Tb3＋ ions in TbF3 nanoparticles.